Polycystin-1 Induces Cell Migration by Regulating Phosphatidylinositol 3-kinase-dependent Cytoskeletal Rearrangements and GSK3β-dependent Cell–Cell Mechanical Adhesion - Boca, Manila (The American Society for Cell Biology, 2007)
Polycystin-1 (PC-1) is a large plasma-membrane receptor encoded by the PKD1 gene mutated in autosomal dominant polycystic kidney disease (ADPKD). Although the disease is thought to be recessive on a molecular level, the precise mechanism of cystogenesis is unclear, although cytoarchitecture defects seem to be the most likely initiating events. Here we show that PC-1 regulates the actin cytoskeleton in renal epithelial cells (MDCK) and induces cell scattering and cell migration. All of these effects require phosphatidylinositol 3-kinase (PI3-K) activity. Consistent with these observations Pkd1−/− mouse embryonic fibroblasts (MEFs) have reduced capabilities to migrate compared with controls. PC-1 overexpressing MDCK cells are able to polarize normally with proper adherens and tight junctions formation, but show quick reabsorption of ZO-1, E-cadherin, and β-catenin upon wounding of a monolayer and a transient epithelial-to-mesenchymal transition (EMT) that favors a rapid closure of the wound and repolarization. Finally, we show that PC-1 is able to control the turnover of cytoskeletal-associated β-catenin through activation of GSK3β. Expression of a nondegradable form of β-catenin in PC-1 MDCK cells restores strong cell–cell mechanical adhesion. We propose that PC-1 might be a central regulator of epithelial plasticity and its loss results in impaired normal epithelial homeostasis.